Hepatic non-parenchymal S100A9-TLR4-mTORC1 axis normalizes diabetic ketogenesis - Gloria Ursino; Giorgio Ramadori; Anna Höfler; Soline Odouard; Pryscila D. S. Teixeira; Florian Visentin; Christelle Veyrat-Durebex; Giulia Lucibello; Raquel Firnkes; Serena Ricci; Claudia R. Vianna; Lin Jia; et al. (Nature Communications, 2022)
Excess ketogenesis can lead to ketoacidosis, a serious complication in patients with diabetes. Here the authors report an insulin independent pathway, the hepatic nonparenchymal S100A9-TLR4-mTORC1 axis, that is able to normalize diabetic ketogenesis and pre-clinical data to suggest potential for development of S100A9 based adjunctive therapy to insulin.